2017
DOI: 10.1007/s00264-017-3514-2
|View full text |Cite
|
Sign up to set email alerts
|

Antero-lateral minimally invasive plate osteosynthesis (MIPO) with the radial nerve exploration for extra-articular distal-third diaphyseal fractures of the humerus

Abstract: Level IV, case series, treatment study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…3 In recent randomized controlled trials, operative management showed better outcomes compared to functional bracing in the treatment of humeral diaphyseal fractures including distal third humeral shaft fractures. 4,5 To address the surgical treatment of distal diaphyseal humeral fractures, several approaches can be used, [6][7][8][9][10] depending on the fracture features or status of the patient. If the fracture line is extended to or over the metaphysis, limited bone stock would be available for sufficient screw fixation via a conventional anterolateral approach.…”
Section: Introductionmentioning
confidence: 99%
“…3 In recent randomized controlled trials, operative management showed better outcomes compared to functional bracing in the treatment of humeral diaphyseal fractures including distal third humeral shaft fractures. 4,5 To address the surgical treatment of distal diaphyseal humeral fractures, several approaches can be used, [6][7][8][9][10] depending on the fracture features or status of the patient. If the fracture line is extended to or over the metaphysis, limited bone stock would be available for sufficient screw fixation via a conventional anterolateral approach.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent cause of iatrogenic nerve injury is interruption of the nerve continuity during surgery or medical procedure [ 19 ]. Zhao et al [ 20 , 21 ] emphasized that precision for the exploration of the radial nerve was essential to avoid nerve iatrogenic injuries. How to achieve radial nerve exposure remains a challenge for the orthopaedic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent cause of iatrogenic nerve injury is interruption of the nerve continuity during surgery or medical procedure [19]. Zhao et al [20,21] emphasized that precision for the exploration of the radial nerve was essential to avoid nerve iatrogenic injuries. How to achieve radial nerve exposure remains a challenge for the orthopaedic surgeon.…”
Section: Discussionmentioning
confidence: 99%